Cleopatra VII Philopator and the Legitimation of Ptolemaic Power - Arroyo de la Fuente, Mª Amparo (Eikón / Imago, 2013)
The various forms of legitimation of power used during the Ptolemaic era were characterized, from the very beginning of the dynasty, by a double conception: on one hand, those images intended for the Egyptian population freed from Persian domination and, on the other hand, those aimed at the Greek settlers from the recently-founded cities, particularly, Alexandria. The legitimation of Hellenistic type would be based on the image of Alexander the Great; on the contrary, the consolidation of Ptolemaic power among the native population was built according to the traditional formulas of power legitimation distinctive of the Pharaonic era. In the case of the last of the Ptolemaic rulers, Cleopatra VII Philopator, this particular iconographic dichotomy was enriched with a new vision of the queen, caused by the need to elaborate and spread her image, not only within the country, but in the Roman Empire as well.